Matching spatial scales of variation in mussel recruitment and adult densities across southwestern Atlantic rocky shores - Arribas, Lorena Pilar (2015)
The recruitment of aquatic invertebrate larvae often differs in space and time thus contributing to variation in the abundance of adults. In the present study, we examined spatial scales of variation in mussel (Brachidontes spp.) recruitment and adult abundance across rocky intertidal areas in the Southwestern Atlantic. Recruitment and adult densities were compared between two regions separated ca. 700 km from each other, two locations (10–20 km from each other) within each region, and two sites (100–500 m from each other) within each location. Variance components analysis indicates that most variation in mussel recruitment and adult densities occurs at the scale of locations, irrespective of if mussel recruitment is quantified on mussel bed samples or artificial substrates (plastic mesh collectors). Increased mussel recruitment and adult densities at this scale are associated with higher time-averaged chlorophyll a concentration and wave exposure, which can potentially affect the supply of larvae to rocky shores by increasing their survival and delivery rates. There was close correspondence between the spatial patterns of variation in cumulative recruitment on natural substrates during the study period and the density of adults at its end. This suggests that differences in mussel abundance along Southwestern Atlantic rocky shores could be primarily determined by larval recruitment.